(untitled) (Móin-Móin Magazine - Studies in the Art of Puppetry, 2024)
This article aims to record the international exchanges that Grupo Sobreventopromoted in the field of Theater of Objects, highlighting the contribution that each of them had in their research and in the dissemination of Theaters of Objects in Brazil.